Non-Epileptic Seizures with Interictal Spikes - J Gordon Millichap (Pediatric Neurology Briefs, 1997)
Long-term EEG-video-monitoring (LTM) detected 12 (8%) patients with non-epileptic seizures (NESs) among 145 temporal lobectomy candidates with medically refractory seizures and interictal temporal EEG spikes in a study at Emory University School of Medicine, Atlanta, GA.